SPECIFICS AND DYNAMICS OF THE MEANING OF CHRONIC PAIN EXPERIENCES TO PATIENTS WITH DEPRESSION - Tatyana Telbizova; Ivan Aleksandrov (Peytchinski Publishing, 2022)
Depression is a psychological factor that affects not only the pain sensation but also the pain experiences. Purpose: The aim of the study was to analyze and summarize the specifics and dynamics of chronic pain experiences in patients with depression. Materials and methods: A sample of 120 patients with chronic pain was studied. Sixty-one patients had clinically manifested depressive episodes, and the other fifty-nine - had no depression. The study was phased. The second stage was performed three months after the first. The patients with depression received antidepressant treatment between the two stages. The sample was evaluated with: 1) quantitative methods: HAM-D-17 for the severity of depression, Spielberger's questionnaire for state and trait anxiety degree and VAS for pain intensity; and 2) qualitative method - content-analysis of the answers to the question "What does pain mean to you?". Results: The mean age of the sample was 51.90 (SD=11.94). Women predominate (81.7%) over men (18.3%). The group with depression had a high degree of state and trait anxiety and moderate pain intensity. The content-analysis revealed that the experience of pain as punishment was specific for patients with depression. The reduction of the mean value of the severity of depression from moderate to mild in the second stage influenced the dynamics of the pain experiences in the direction of a limitation. Conclusion: Depression is a factor influencing the meaning of chronic pain experience. The search for depressive symptoms and specific experiences and their intervention is substantial in the management of chronic pain.